Manajemen taman kanak-kanak strawbery di desa blender kecamatan karangwareng kabupaten cirebon - Putri, Khairunnisa Aulia; Zahra, Khoirina Az; Faridah, Raissa Nur; Salma, Syakurah (ARKA INSTITUTE, 2022)
This study aims to understand the management of the Strawbery Kindergarten in Cirebon City, West Java. This research uses a qualitative case study approach. The data collection technique is done through interviews, observation and documentation. While the data analysis technique starts from data display, data reduction, to drawing conclusions. The results showed that; First, this Strawaberry Kindergarten curriculum still uses K13; second, there are still many educators at Strawaberry Kindergarten who do not meet the qualification requirements for PAUD teachers; third, the constraint of the shortage of educational personnel owned by TK Strawbery; fourth, the success of student management in Strawbery Kindergarten.